Microscopically and Molecular Detection of Theileria Species in Sheep in Baghdad Province, Iraq - Azhar Faraj; Dhirar Assi (مجلة الانبار للعلوم البيطرية)
The study was conducted to estimate the prevalence of Theileriosis in sheep in Baghdad city, as well as study the effect of age, sex, and months in the infection rate by examination of 180 of blood samples collected during the period from the beginning of October 2020 to the end of March 2021. All samples were examined by microscopic examination, and 100 blood samples collected randomly from total 180 were molecular detection by using conventional PCR. The total infection rate of the microscopic infection was 33.33%(60/180). The result showed a significant difference (P<0.05) between two different ages of animals that infected with Theileria spp and the adult sheep(>1y), which recorded the higher 50% (50/100), while the lower infection rate 12.5% (10/80) was among the young sheep(6mns-1y). concerning sex and months, there was no significant difference between female and male ,also among study months. The conventional PCR technique was used in the molecular study; 70(70%) out of 100 blood samples were selected randomly from 180 sheep. PCR products of teen were selected randomly for DNA analysis to obtain the partial nucleotides sequence of 18S ribosomal RNA gene . The PCR product was processed as a wave-like shape at (1104bp) after that sequences were recorded in NCBI with No.1 (MW735685.1), No.2(MW735686.1), No.3 (MW735687.1), No.5 (MW735689.1),No.7 (MW735691.1),No.8 (MW735692.1), No.10 (MW735694.1) for Theileria ovis and No.1 No.4 (MW735688.1), No.6 (MW735690.1), No.9 (MW735693.1) for Theileria